1D.07: LONG-TERM OUTCOME AFTER ANGIOPLASTY IN PATIENTS WITH RENAL ARTERY STENOSIS AND HIGH RESISTIVE INDEX. (June 2015) - Limbourg, F.; Scherer, N.; Hiss, M.; Haller, H.; Radermacher, J.
Abstract : Objective: The benefit of revascularization for renal artery stenosis is currently unclear. A number of prospective, randomised studies showed no advantage of interventional revascularization (PTA) over medical therapy apart from a reduction in the number of antihypertensive drugs. A predictor of a more positive response to interventional treatment is urgently needed. We have shown that patients with a high resistive index (RI, > 80) by Doppler ultrasonography have inferior outcome after interventional revascularization for renal artery stenosis. We here obtained long-term follow up data from the original study collective and compared this to a matched group of recent patients with high resistive index which did not undergo revascularization but had improved medical therapy. Figure. No caption available. Design and method: We measured the renal RI with Doppler ultrasonography in segmental arteries of both kidneys. 131 patients underwent renal angioplasty, 35 of these had renal RI values > 80. A further group of 31 patients with RI > 80 and renal artery stenosis > 65% did not undergo angioplasty. The combined endpoint was > 50 percent decrease in eGFR, end stage renal failure, or death. Mean (± SD) follow-up was 8.8 ± 4 years. Results: In patients with high RI (> 80), a decrease in renal function occurred in 74% patients after PTA and 77% without PTA compared to 19% of those with PTA and low RI. 71% and 52% of patients, compared to 17%, required dialysis, and 89% and 48% compared to 31% died (p<0.001 high RI compared to low RI). A total of 94% and 90% with high RI reached the combined endpoint as compared to 39% of those with low RI (multivariate relative risk 16, CI 3.7 to 68; P < 0.001 high RI vs low RI). Conclusions: Patients with renal artery stenosis and a high renal resistive index do not benefit from angioplasty in long-term follow up for renal and patient survival. Patients with high resistive index continue to suffer a poor prognosis even under improved medical therapy.